Quantum mechanical tunnelling through the catalytic effects of A2451 ribosomal residue during a stepwise peptide bond formation - Monajemi, Hadieh; Zain, Sharifuddin Md; Ishida, Toshimasa; Wan Abdullah, Wan Ahmad Tajuddin (Canadian Science Publishing (NRC Research Press), 2019)
The search for the mechanism of ribosomal peptide bond formation is still ongoing. Even though the actual mechanism of peptide bod formation is still unknown, the dominance of proton transfer in this reaction is known for certain. Therefore, it is vital to take the quantum mechanical effects on proton transfer reaction into consideration; the effects of which were neglected in all previous studies. In this study, we have taken such effects into consideration using a semi-classical approach to the overall reaction mechanism. The M06-2X density functional with the 6-31++G(d,p) basis set was used to calculate the energies of the critical points on the potential energy surface of the reaction mechanism, which are then used in transition state theory to calculate the classical reaction rate. The tunnelling contribution is then added to the classical part by calculating the transmission permeability and tunnelling constant of the reaction barrier, using the numerical integration over the Boltzmann distribution for the symmetrical Eckart potential. The results of this study, which accounts for quantum effects, indicates that the A2451 ribosomal residue induces proton tunnelling in a stepwise peptide bond formation. © 2019 Published by NRC Research Press.